Measuring the origins of macroeconomic uncertainty - Haroon Mumtaz (Queen Mary University of London, School of Economics and Finance, 2018)
This paper extends the procedure developed by Jurado et al. (2015) to allow the estimation of measures of uncertainty that can be attributed to specific structural shocks. This enables researchers to investigate the "origin" of a change in overall macroeconomic uncertainty. To demonstrate the proposed method we consider two applications. First, we estimate UK macroeconomic uncertainty due to external shocks and show that this component has become increasingly important over time for overall uncertainty. Second, we estimate US macroeconomic uncertainty conditioned on monetary policy shocks with the results suggesting that while policy uncertainty was important during early 1980s, recent contributions are estimated to be modest.
Keywords: C2; C11; E3; 330; FAVAR; Stochastic volatility; Proxy VAR; Uncertainty measurement